Assessing Gombe State Citizens’ Attitude And Perception Towards Nigeria’s Cashless Policy - Bachama, Yusufu Nigel; Bello, Matthew Funsho (FIA UB, 2021)
The Central Bank of Nigeria (CBN) introduced the cashless policy in 2011, which eventually took effect in 2012. The aim of the policy amongst others is to reduce the amount of physical cash circulating in the economy and encouraging more electronic-based transactions. The objective of this study is to review the CBN cashless policy in Gombe State and assess peoples’ behavior and attitudes towards the policy in the State since its inception. Questionnaires were administered on 300 bank customers across the 11 Local Government Areas (LGAs) of the State. The findings revealed that 65% of respondents do not know what the cashless policy is all about, 80% are happy with the introduction of cash-lite (Cashless) points such as Automated Teller Machines, Point of Sales, and Internet Banking etc. As an interim verdict, 25% of the respondents believe that the cashless policy is necessary, 24% believe that the CBN approach to its implementation is the best and 43% believe that the policy will succeed. The study recommends that more banks’ branches and cash-lite channels need to be established especially in other LGAs; there is also the need to consolidate in infrastructural development; and financial literacy for all.